Towards AGV Optimization using ROS and Stage Simulator - Silva, Bruno Carneiro da (2020)
Autonomous Guided Vehicles (AGV) are currently being used in industry to move materials efficiently. Simulators may be used to help calculate the right number of AGVs needed for a particular task and also which types better suit the necessity of a company. This paper analyzes the characteristics of many of the most used simulators and focus on evaluating an environment using Stage and Robot Operating System (ROS), to find experimentally if one AGV may complete a specific task taking into account eventual path blockages by random events.